Analysis of Students University Understanding of Juvenile Criminal Decisions from the Perspective of Legal Education - Siswanto, Siswanto; Samsuddin, Samsuddin (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
This study examines As'adiyah Sengkang Islamic University (UNISAD) students' understanding of juvenile criminal decisions in legal education. The Juvenile Criminal Justice System Law (UU SPPA No. 11 of 2012) requires child protection principles like diversion and restorative justice, but students at the Faculty of Sharia and Islamic Law (FSHI) UNISAD may not understand them when analyzing court decisions. This study examines how students internalize the child protection paradigm and how the Islamic legal education curriculum shapes their views on juvenile criminalization. The method is empirical legal study utilizing quantitative and qualitative methods. Primary data was collected from FSHI students who took juvenile criminal law courses using standardized questionnaires and in-depth interviews. Patterns and comprehension were found using descriptive data analysis. The results indicate that kids comprehend diversion theoretically. When presented with real-life decision cases, their understanding tends to revert to a retributive approach (conventional punishment), indicating that campus legal education has not fully transformed their thinking paradigm to a comprehensive child protection perspective. This project provides data-driven feedback for the FSHI UNISAD to improve juvenile criminal justice teaching techniques and curriculum. To make legal education more relevant, graduates should know sharia theory and positive law and be sensitive and competent to monitor restorative justice methods in juvenile criminal justice.